Criminal Law Aspect of Illegal Transshipment Under Act Number 45 of 2009 Concerning Fisheries - Herman Herman; Oheo K Haris; Syahbudin Syahbudin (Universitas Airlangga, 2021)
This study aims to analyze the practice of illegal transshipment in compliance with Act Number 45 of 2009 criminal provisions law concerning Fisheries, using legal concept, law, and case approaches. Nowadays, there are various operational modes of fish theft, with poor regulations that maximally accommodate crimes related to fisheries by perpetrators. Therefore, due to its unsustainability and economic loss, the fisheries and marine sector in Indonesia has to improve its performance. The results show that illegal transshipment engages some elements contained in Article 94 and 94A of Act Number 45 of 2009 which was an amendment of Act Number 31 of 2004. According to article 94, when a fishing vessel is caught transferring shipment in the middle of a high sea without in possession of a license called SIKPI, its owner/s are sentenced to 5-years imprisonment with a one billion five hundred million rupiah fine. Meanwhile, according to Article 94A, when a fishing vessel is caught using fake licenses such as SIUP, SIPI, and SIKPI, its owners are sentenced to 7 years imprisonment with a fine of three billion rupiahs.